An Intelligent Resource Manager Over Terrorism Knowledge Base - Patel, Archana; Sharma, Abhisek; Jain, Sarika (Recent Advances in Computer Science and Communications, 2020)
The complex and chaotic crisis created by terrorism demands for situation awareness which is possible with the proposed Indian Terrorism Knowledge Treasure (ITKT). Objective: This work is an effort at creating the largest comprehensive knowledge base of terrorism and related activities, people and agencies involved, and extremist movements; and providing a platform to the society, the government and the military personnel in order to combat the evolving threat of the global menace terrorism. Methods: For representing knowledge of the domain semantically, an ontology has been used in order to better integrate data and information from multiple heterogeneous sources. An Indian Terrorism Knowledge Base is created consisting of information about past terrorist attacks, actions taken at time of those attacks, available resources and more. An Indian Terrorism Resource Manager is conceived comprising of various use cases catering to searching a specified keyword for its description, navigating the complete knowledge base of Indian Terrorism and finding any answers to any type of queries pertaining to terrorism. Results: The managerial implications of this work are two-fold. All the involved parties, i.e., the government officials, military, police, emergency personnel, fire department, NGOs, media, public etc will be better informed in case of emergency and will be able to communicate with each other; hence improving situation awareness and providing decision support.
Keywords: knowledge treasure